Aviation Analytics - Goel, Shobhit; Kavitha V,; Pragada, Suraj (International Journal of Psychosocial Rehabilitation, 2020)
The role of global aviation industry has a level of dependence everywhere , even for the transportation and as well as for other sectors, everyday a very large amount data such as passenger details etc has been stored and processed in the warehouses